Keterkaitan spasial infrastruktur fisik dan pertumbuhan ekonomi wilayah di Pulau Jawa - Gabriel Ivo Aveliano Kusuma Adi Valentino; Amirullah Setya Hardi (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Physical infrastructure development is a key instrument for promoting regional economic growth, particularly in Java as the center of national development activities. However, infrastructure development also generates varying spillover effects across regions. This study aims to analyze the impact of physical infrastructure on regional economic growth in six provinces on Java Island during the 2011–2022 period. Infrastructure variables include the length of public roads, toll roads, airport cargo activity as a proxy for airports, port cargo activity as a proxy for seaports, electricity sold, and the Construction Cost Index. Data were obtained from Statistics Indonesia (BPS), the Ministry of Public Works and Housing, the Ministry of Transportation, and CEIC Data. Spatial regression analysis using the Spatial Durbin Model (SDM) was applied to identify both direct effects and interregional spillover effects. The results show that the highest economic growth occurred in DKI Jakarta, while the spatial distribution of spillover effects across provinces is not clustered. Public road length and airport proxies have a significant positive impact on economic growth with positive spillover effects on neighboring regions. In contrast, toll road length exhibits a negative spatial effect with negative spillovers. Meanwhile, port proxies generate positive spillover effects. These findings indicate the need for careful consideration in infrastructure development planning to ensure alignment with regional interactions and balanced regional development.